Interactive Gene Expression Between Metarhizium anisopliae JEF-290 and Longhorned Tick Haemaphysalis longicornis at Early Stage of Infection - Lee, Mi Rong; Kim, Jong Cheol; Park, So Eun; Lee, Se Jin; Kim, Woo Jin; Lee, Doo-Hyung; Kim, Jae Su (Frontiers in Physiology, 2021)
The longhorned tick (LHT), Haemaphysalis longicornis (Acari: Ixodidae), is a hard tick and a vector for severe fever with thrombocytopenia syndrome (SFTS) virus. The number of patients infected with SFTS is rapidly increasing. Recently, the invertebrate pathogen Metarhizium anisopliae JEF-290 was reported to be useful to control the tick as an alternative to chemical acaricides, which are not easily applicable in human living areas where the tick is widely spread. In this study, we analyzed how the LHT and the fungal pathogen interact at the transcriptional level. Field-collected LHT nymphs were treated with JEF-290 conidia at 1×108 conidia/ml. In the early stage of infection with 2.5% mortality, the infected ticks were subjected to RNA sequencing, and non-infected ticks and fungal masses served as controls. Fungus and tick genes were mostly up-regulated at the early stage of infection. In the gene set enrichment analysis of the infecting fungus, catabolic processes that included lipids, phospholipids, and detoxification processes, the response to oxidative stress, and toxic substances were significantly up-regulated. In this fungal up-regulation, various lipase, antioxidant enzyme, and hydrolase genes were highly transcribed. The gene set enrichment analysis of the infected tick showed that many peptide synthesis processes including translation, peptide metabolism, ribonucleotide metabolism, and energy production processes that included ATP generation and ADP metabolism were significantly up-regulated. Structurally, mitochondria and ribosome subunit genes in ticks were highly transcribed to upregulate these processes. Together these results indicate that JEF-290 initiates process that infects the LHT while the LHT actively defends against the fungal attack. This work may provide a strong background to improve our understanding of the early stage of fungal infection in LHT.